Historical Materialism Seen Through the Lens of Magical Realism: Gender Relationships in ‘Nights at the Circus’ - Emilija Dimitrijevic (Linguae &: Rivista di Lingue e Culture Moderne, 2015)
Nights at the Circus (1984) by Angela Carter is widely recognized as a masterpiece of magical realism. At the same time, the novel stands out in the literary genre because of its distinctly materialistic outlook. This essay argues that specific to Carter’s writing is the view of gender discourse as yet another form of idealization of dominant economic relationships. Classical Marxist theory begins with the analysis of capitalism under the Industrial Revolution and extends it to consider its implications in less developed economies. The novel proceeds similarly: it starts with gender relationships most obviously fashioned as economic transactions but explained away as natural, moves on to those apparently less governed by economic interests, and finally examines gender relationships where they appear to be dominated by the supernatural, showing that in all these cases economic relationships are not less decisive but rather differently naturalized.